2020
DOI: 10.3168/jds.2020-18235
|View full text |Cite
|
Sign up to set email alerts
|

The use of ensiled olive cake in the diets of Friesian cows increases beneficial fatty acids in milk and Halloumi cheese and alters the expression of SREBF1 in adipose tissue

Abstract: This study aimed to evaluate the effect of dietary inclusion of ensiled olive cake, a by-product of olive oil production, on milk yield and composition and on fatty acid (FA) profile of milk and Halloumi cheese from cows. Furthermore, the effect of olive cake on the expression of selected genes involved in mammary and adipose lipid metabolism was assessed in a subset of animals. A total of 24 dairy cows in mid lactation were allocated into 2 isonitrogenous and isoenergetic feeding treatments, named the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 57 publications
(105 reference statements)
3
16
0
4
Order By: Relevance
“…It has been reported that heating, the fermentation culture used, and the ripening time required for the production of cheese could potentially modulate cheese FA composition [ 4 ]. However, in our previous studies [ 28 , 54 ], the FA profiles of milk and related Halloumi cheese produced were similar, which suggested that the improvement in nutritional quality achieved in milk due to organic practices is possibly further maintained in organic Halloumi cheese in the present study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It has been reported that heating, the fermentation culture used, and the ripening time required for the production of cheese could potentially modulate cheese FA composition [ 4 ]. However, in our previous studies [ 28 , 54 ], the FA profiles of milk and related Halloumi cheese produced were similar, which suggested that the improvement in nutritional quality achieved in milk due to organic practices is possibly further maintained in organic Halloumi cheese in the present study.…”
Section: Discussionsupporting
confidence: 58%
“…The cheese fat was extracted with diethyl ether according to the method described by Neofytou et al [ 28 ]. Briefly, 50 mL of diethyl ether and 0.5 g of Na 2 SO 4 was added to 30 to 40 g of cheese samples and mixed vigorously.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the low nutritive value of this by-product (Hadjipanayiotou 1999;Abbeddou et al 2015), its use may be promoted to the farmers and subsequently to the halloumi cheese manufacturers due to likely beneficial effects on fat quality. Our previous study using this ensiled OC by-product in cow diets at a rate of 10% DM showed improved lipid profile in both bovine milk and related halloumi cheese produced regarding total unsaturated lipids, atherogenicity indices, and particularly beneficial fatty acids (FA) such as conjugated linoleic acid (CLA 18:2 cis-9, trans-11, rumenic acid (RA)) and oleic acid content (Neofytou et al 2020). It is not known, however, if higher diet inclusion of OCS on diets may be used on sheep conferring any additional benefits on the quality of ovine milk and ovine halloumi cheese without detriments on milk production and/or intake.…”
Section: Introductionmentioning
confidence: 94%
“…Proposed processing methods such as drying and partly destoned and dried (Abbeddou et al 2011a(Abbeddou et al , b, 2015, inclusion into multi-nutrient blocks (Molina-Alcaide et al 2010), or pelleted with other ingredients (Castellani et al 2017) add extra cost, time, and labor and therefore possibly outweigh its usefulness as an affordable forage substitution alternative. However, a cost-effective method of OC preservation is suggested by researchers in Cyprus (Hadjipanayiotou 1999;Symeou et al 2019;Neofytou et al 2020) through silage preparation using fresh OC, shortly after production, without any costs of processing or additives (olive cake silage, OCS), allowing extended storage time and consequently use throughout the year as a forage alternative.…”
Section: Introductionmentioning
confidence: 99%
“…These results were confirmed by the positive correlation found between NE-DNA complexes produced during NETosis and intracellular H 2 O 2 controlled by MPO activity, and were probably due to the major content of OA in the OP diet found in the present study. Neofytou et al ( 72 ), supplementing cows with 10% of ensiled olive cake, with a level of OA of about 30% of the dietary lipids, observed a reduction of medium-chain FA concentration and increased long-chain FA (LCFA) levels in cow's milk ( 72 ). The direct transfer between blood to milk constituent ( 73 ) could suggest that OA from the diet could have represented a suitable energy source to initiate an effective neutrophil response.…”
Section: Discussionmentioning
confidence: 99%